Republic of Lithuania : Financial Sector Assessment Program Update-Technical Note-Insolvency and Creditor Rights Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Technical Note discusses key findings of the insolvency and creditor rights assessment for Lithuania. Lithuania has made significant progress in the field of creditor rights legislation and related institutions. Under the current legal framework, the creation and registration of secured transactions is rather easy and affordable. The privatization of the bailiffs system has contributed to accelerating the recovery process and increasing the enforcement efficiency. In the area of corporate insolvency, the Enterprise Bankruptcy Law and the Law on Restructuring of Enterprises are generally consistent with international standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; Insolvency Administrator; Insolvency; ISCR; Judge; Lithuania, Republic of